2013 IEEE 63rd Electronic Components and Technology Conference 2013
DOI: 10.1109/ectc.2013.6575782
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of the Cu/Al interface in Cu-Wire-bonded integrated circuits

Abstract: A model for corrosion induced failure in wire bond devices made with either Cu or Au wire was developed. The model is based on detailed analysis of the chemical composition, crystallography, and microstructure of the corrosion induced failure sites. The detailed analysis was enabled by both a scanning electron microscope (SEM) and a transmission electron microscope (TEM) equipped with the appropriate analytical detectors.The combined characterization results were used to develop a detailed failure mechanism mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…This is because CuAl 2 was corroded by Chlorine from molding compound resulting in Cu reduction. [13] However, no obvious damage was found at the interface between Cu and Al after 1056h of biased-HAST as shown in Figure 7(b). Figure 7(d) is the enlarged image of the selected area of Figure 7(b).…”
Section: Biased-hastmentioning
confidence: 86%
See 1 more Smart Citation
“…This is because CuAl 2 was corroded by Chlorine from molding compound resulting in Cu reduction. [13] However, no obvious damage was found at the interface between Cu and Al after 1056h of biased-HAST as shown in Figure 7(b). Figure 7(d) is the enlarged image of the selected area of Figure 7(b).…”
Section: Biased-hastmentioning
confidence: 86%
“…Presumably the CuAl 2 should be corroded during biased-HAST testing. [8,13] The corrosion behavior will discuss later. Figure 7 represents the cross section images of failed bare Cu wire and Pd/Cu wire with high Cl -molding compound after 1056h of biased-HAST.…”
Section: Biased-hastmentioning
confidence: 99%
“…Furthermore, its higher modulus reduces wire sweep concern for fine pitch wire bonding. However, there are some drawbacks of Cu wire in terms of material properties which raise reliability concern and decrease productivity: (a) Cu is much harder than Au, no matter wire or FAB, the structureunderneathbondpad of the IC chip is more susceptible to be damaged, which narrows the wire bonding process window [2]; (b) Cu wire bonding makes serious "Al splash" compared to Au wire bonding, which hinder finer bond pad pitch design [2]; (c) CuAl IMC (intermetallic compound) is reported to have shorter HAST life than AuAl IMC's, which causes reliability concern [3,4]; (d) Cu wire bonding is challenging to apply to stackeddie configuration and dietodie wire bonding, due to its high hardness and stiffness; (e) Cu is susceptible to be oxidized, the bondability of second bond is impacted, although Pd coated or Pd/Aucoated Cu wire can alleviate this problem, however material cost increasing as a penalty; finally, (f) Cu wire bonding has lower production throughput as well as process yield, in general, this is due to its high hardness (requiring longer bonding time and larger bonding power) and narrower process window (implying lower yield).…”
Section: mentioning
confidence: 99%
“…Experiments by Osenbach et al [11] show selective oxidation of the Al in Cu 9 Al 4 that results in the formation of a two-phase microstructure composed of γ-Al 2 O 3 with embedded crystalline Cu metal particles. We use a simplified model for the corrosion reaction following [11]:…”
Section: Modelmentioning
confidence: 99%
“…Even though Al is the most electrochemically active, Al passivation oxides prevent the corrosion of Al and Alrich IMCs. Passivation oxide pitting is observed primarily in the Cu 9 Al 4 and therefore, this is the first phase to be corroded [9][10][11][12][13]. Boettcher et al [13] observed the resulting oxidized interface which is highly susceptible to fracture and therefore, the ultimate reason for failure.…”
Section: Introductionmentioning
confidence: 99%